Identification of α-Amylase Inhibitory Peptides from Tryptic Hydrolysate of Caulerpa racemosa Green Algae Protein - Husna, Izatul; Habibie, Ahmad; Astuti, Endang; Raharjo, Tri Joko (Universitas Gadjah Mada, 2025)
Peptides have been reported as a potential alternative for antidiabetic therapy by inhibiting α-amylase, one of the key enzymes involved in carbohydrate metabolism. This study aimed to identify α-amylase inhibitory peptides derived from trypsin hydrolysate of Caulerpa racemosa protein. The protein was extracted using trichloroacetic acid (TCA)/acetone. The resulting peptides were fractionated using a strong cationic exchanger-solid phase extraction (SCX-SPE) column. The peptide fractions were tested for α-amylase inhibitory activity, and the peptides in the most active fraction were identified using liquid chromatography-high resolution mass spectrometry (LC-HRMS). Seven fractions were obtained from SCX-SPE elution at pH 3 to 9. The fraction eluted at pH 5 exhibited the highest α-amylase inhibitory activity, with an IC50 value of 43.70 µg/mL. Four peptides with the sequences VQKEKR, MNFYCISSK, DLCDYIHNK, and ISICYEK were identified from this fraction. Molecular docking studies revealed that the peptides with sequences MNFYCISSK and VQKEKR had the strongest interactions with α-amylase. The peptide binding affinity energies of MNFYCISSK and VQKEKR were −10.3 and −9.4 kcal/mol, respectively, with RMSD values of 0.3 ± 0.0 and 0.3 ± 0.2 Å. It can be concluded that the peptides with sequences MNFYCISSK and VQKEKR could be proposed as potential antidiabetic peptides with an α-amylase inhibition mechanism.